How and Why the Quyllurit’i Pilgrimage Is Related to the Tupac Amaru Rebellion. - Salas Carreño, Guillermo (Latin American Research Review, 2026)
This article analyzes historical claims about the Quyllurit’i pilgrimage (Cuzco, Peru). First, it discusses its relationship to Inka rituals and the Tupac Amaru rebellion. It shows that the way the rebellion affected the Ocongate church in 1782 was crucial for the later inscription of 1783 as the year of the pilgrimage’s miracle. It then analyzes how the conflicts between the Ocongate merchants and the hacienda Lauramarca over the commercialization of colono alpaca wool in the late nineteenth and early twentieth centuries are related to the creation of the first written account of the pilgrimage’s origins. This account was written in 1932, using the local archive shaped by the Great Rebellion, but without any evidence of anything that happened in 1783 in what is now the Quyllurit’i shrine. As the pilgrimage expanded beyond Ocongate, scholars who studied the pilgrimage in the 1970s used this first account to hypothesize its relationship to the Great Rebellion within tropes of indigenous cultural authenticity, continuity, and resistance.